Analysis of the Impact of the Industrial Existence of PT. Lombok Gandaria to the Socio-Economic Condition of Dagen Village, Jaten District, Karanganyar Regency - Latifah Hanisa Prihapsari; Priyono Priyono (Amcolabora, 2023)
PT. Lombok Gandaria is an industry engaged in food in Karanganyar Regency, precisely in DagenVillage. The existence of industry in the midst of society has a social and economic impact. Theobjectives of this study are (1) to examine the socio-economic characteristics of the Dagen Villagecommunity af ected by the presence of industry and (2) to examine the impact of the Dagen Villagecommunity's socio-economic conditions on the existence of the industry. The type of this research isdescriptive quantitative which is presented with a table, while the method in this research is a surveywith data acquisition using a questionnaire and to determine the sample using the purposive samplingmethod with the Slovin formula. The results showed that the existence of PT Lombok Gandaria's SoySauce Factory in Dagen Village had both positive and negative impacts on the community. Thepositive impact of the factory in the form of the availability of jobs, reduce unemployment, providebusiness opportunities and af ect the income of traders. Meanwhile, the negative impact is in the formof a very pungent smell of sewage and is disturbed by vehicles passing through the village.